Comparative growth and yield of taro (Colocasia esculenta) accessions cultivated in the Western Cape, South Africa - Lewu, M.N.; Mulidzi, A.R.; Gerrano, A.S.; Adebola, P.O. (Friends Science Publishers, 2017)
The growth and yield characteristics of six accessions (Amadumbe 2914, Amadumbe 3053, Amadumbe 43, Amadumbe 56, Amadumbe Amzam 3553/5118 and Amadumbe 2919) of Colocasia esculenta (taro) were compared in the Western Cape Province of South Africa. A randomized complete block design with five replications was used. Differences in growth and yield observed among the accessions may be attributed to non-uniformity in the size of the propagules used for establishment of the trial, genotypic and/or climatic factors. Amadumbe 2914, Amadumbe 3053, Amadumbe 43 and Amadumbe 56, established with bigger cormels (20.37 - 28.33 g) consistently showed superiority in terms of plant height, leaf area and yield over Amadumbe Amzam 3553/5118 and Amadumbe 2919, established with smaller cormels (15.00 and 16.67 g). However, there was no appreciable difference in the size and weight of individual cormels produced by all six accessions. Due to small cormel sizes, a higher proportion (about 92%) of the cormel yield could be classified as unmarketable. Good nutrition can be provided by the leaves and tubers, even though maximum yield may not be attained in the Western Cape due to temperature, radiation and day length limitations, especially in winter. Continued research to determine whether yield can be improved with better nutrition and agronomic practices, is warranted.